Quantifying fluid filling of the air voids in air entrained concrete using neutron radiography. (November 2019) - Khanzadeh Moradllo, Mehdi; Qiao, Chunyu; Hall, Hope; Ley, M. Tyler; Reese, Steven R.; Weiss, W. Jason
Abstract: Knowledge of the degree of saturation in concrete is useful for predicting service-life in a freeze-thaw environment. The degree of saturation increases as a result of fluid absorption. Conventional testing methods to determine fluid absorption (e.g., gravimetric mass measurements) measure cumulative fluid uptake; however, they cannot provide information on the spatial distribution of the absorbed fluid in the sample. Further, conventional test methods cannot determine the degree of saturation at each point in the sample. This paper uses neutron radiography to overcome these limitations and to quantify the volume of water and degree of saturation at each location in the sample. The Powers-Brownyard model is used to calculate pore volume (i.e., matrix pores) that are filled during 1-D capillary water absorption in air-entrained concrete. This information is used to quantify the volume of water in the matrix pores (capillary, chemical shrinkage and gel pores) and the volume of water in the air voids, and subsequently the rate of filling of each pore. This study examined the fluid absorption in concrete mixtures with three different water-to-cement (w/c) ratios (0.40, 0.45 and 0.50) and a range of air contents (2.5%–9.0%). Results show that the air voids filling process is slower than the filling of the matrix pores. The air content has negligible impact on the rate of water ingress in air voids at a given w/c. However, reducing the w/c of a mixture lowers the volume of filled air voids for a comparable period of water ingress due to the lower matrix permeability. As the air content increases, the time-dependent percentage of the air void that is filled (i.e., degree of saturation of air voids) decreases regardless of the w/c.